Polypropylene spunbond non-woven fabric production process based on plasma polymerization modification

A nanocomposite protective layer was constructed on polypropylene spunbond non-woven fabric through plasma etching and gradient self-assembly technology, which solved the problem of easy shedding of functional components, achieved antibacterial, hydrophobic and breathable properties, improved the versatility and durability of the material, and reduced pollution.

CN120625358AInactive Publication Date: 2025-09-12ANHUI YIHE NON WOVEN FABRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510573220.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-09-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polypropylene spunbond non-woven fabrics have the problem that the functional components are easy to fall off, unevenly distributed, and have poor durability during surface coating or blending modification, making it difficult to meet the multifunctional requirements such as antibacterial, hydrophobic, and washable.

Method used

A highly active surface is constructed by argon-oxygen plasma etching, combined with the gradient self-assembly of the copolymer transition layer and the nano-composite protective layer, and the synergistic effect of nano-zinc oxide/polysiloxane is used to form a gradient functional layer, including an ion activation layer, a copolymer transition layer and a nano-composite protective layer.

Benefits of technology

The non-woven fabric has achieved long-term antibacterial, super-hydrophobic and high breathability, with an antibacterial rate of ≥99.5%, which remains ≥95% after 50 washes, a hydrostatic pressure of ≥20kPa, an air permeability of 200-500L/(m2·s), and an environmentally friendly process without solvent pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120625358A_ABST
    Figure CN120625358A_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene spunbond non-woven fabric based on plasma polymerization modification, the polypropylene spunbond non-woven fabric comprises a gradient functional layer, a gradient functional layer base material layer and a surface functional layer, the surface functional layer comprises an inner layer, an interlayer and an outer layer, the inner layer comprises an ion activation layer, the thickness of the ion activation layer is 50-200nm, and the thickness of the interlayer is 50-200nm. The ion activation layer is formed through argon-oxygen mixed plasma etching, and the surface roughness Ra of the ion activation layer is greater than or equal to 0.5 mu m; the interlayer comprises a copolymer transition layer, and the thickness of the copolymer transition layer is 300-800 nm. Through the synergistic effect of the nano zinc oxide and the tannic acid-silver composite coating layer, the good effect that the bacteriostasis rate on staphylococcus aureus is larger than or equal to 99.5% is achieved, the bacteriostasis rate of the non-woven fabric is still kept to be larger than or equal to 95% after the non-woven fabric is washed with water for 50 times, and tannic acid serves as a natural reducing agent and stabilizer, so that the dispersity and antibacterial durability of silver nanoparticles are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonwoven fabric production, in particular to a production process of polypropylene spunbond nonwoven fabric based on plasma polymerization modification. Background Art

[0002] Polypropylene spunbond nonwovens are a type of nonwoven fabric with unique properties and a wide range of applications. Made primarily from polypropylene, spunbond is formed by high-temperature drawing and polymerization into a mesh structure, which is then bonded together using a hot-calendering process. This simple production process offers high yields and is non-toxic and harmless to the human body. Due to its lightweight, high-strength, and low-cost properties, spunbond is widely used in medical protective equipment, sanitary products, and filter materials.

[0003] However, in the existing technology, functional components are often introduced through surface coating or blending modification, but there are defects such as easy shedding of the coating, uneven distribution of functional components, and poor durability. In addition, traditional polypropylene non-woven fabrics have problems such as strong surface inertness and single function, which makes it difficult to meet the multifunctional requirements such as antibacterial, hydrophobic, and washable. Summary of the Invention

[0004] The present invention aims to provide a process for producing polypropylene spunbond nonwovens based on plasma polymerization modification. This process utilizes argon-oxygen plasma etching to create a highly active surface, combined with molecular grafting and crosslinking of a copolymer transition layer, to achieve gradient self-assembly of a nanocomposite protective layer. This technology not only addresses the problem of functional layer peeling in traditional processes but also, through the synergistic effect of nano-zinc oxide / polysiloxane, imparts the nonwoven with the combined properties of long-lasting antimicrobial properties, super-hydrophobicity, and high breathability. This overcomes the technical bottleneck of the single function of existing polypropylene nonwovens and addresses the issues raised in the aforementioned background technology.

[0005] To achieve the above-mentioned object, the present invention provides the following technical solution: a polypropylene spunbond non-woven fabric modified by plasma polymerization, comprising a gradient functional layer, a gradient functional layer substrate layer and a surface functional layer, the surface functional layer comprising an inner layer, an interlayer and an outer layer, the inner layer comprising an ion activation layer, the ion activation layer having a thickness of 50-200 nm, the ion activation layer being formed by argon-oxygen mixed plasma etching, and the surface roughness of the ion activation layer being Ra ≥ 0.5 μm; the interlayer comprising a copolymer transition layer, the copolymer transition layer having a thickness of 300-800 nm, the copolymer transition layer being copolymerized by acrylic acid and vinyl pyrrolidone in a molar ratio of 1:0.3-0.8, and the grafting rate of the copolymer transition layer being 25%-45% acrylic acid / vinyl pyrrolidone copolymer transition layer; the outer layer comprising a nano-composite protective layer, the nano-composite protective layer having a thickness of 100-500 nm, the nano-composite protective layer comprising a composite of nano-zinc oxide and polysiloxane having a particle size of 10-30 nm, wherein the mass proportion of the nano-zinc oxide is 3-8%.

[0006] A polypropylene spunbond nonwoven fabric modified by plasma polymerization and a production method thereof, comprising

[0007] Step S1: placing a polypropylene spunbond nonwoven fabric substrate in a vacuum plasma reaction chamber, introducing an argon-oxygen mixed plasma gas, and treating for 5-8 minutes at a power of 80-120 W and a pressure of 20-50 Pa to form an ion activation layer;

[0008] Step S2: acrylic acid and vinyl pyrrolidone monomers are mixed in proportion, a crosslinking agent and an initiator are added, and the mixture is sprayed on the surface of the activation layer by atomization. The mixture is reacted at 60-80° C. for 1-3 hours under a nitrogen atmosphere to form a copolymer transition layer;

[0009] Step S3: spraying the nano zinc oxide dispersion and the polysiloxane prepolymer alternately on the surface of the transition layer, curing each layer at 120-150° C. for 10-30 seconds after spraying, and repeating 5-15 times to form a gradient nano composite protective layer.

[0010] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, wherein the zinc oxide nanoparticles in the nano-composite protective layer are distributed in a gradient, and the surface concentration of the gradient-distributed nano zinc oxide is higher than the bottom concentration, wherein the surface concentration is 5-8wt% and the bottom concentration is 1-3wt%.

[0011] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, wherein the volume ratio of argon to oxygen in the argon-oxygen mixed plasma is 4:1-8:1, the plasma treatment power is 50-150W, the treatment time is 3-10 minutes, the surface oxygen content of the ion activation layer is ≥15at%, and the surface after etching forms a nanoscale pit array with a pit depth of 50-200nm.

[0012] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, wherein 0.5-2% by weight of azobisisobutyronitrile is introduced into the copolymer transition layer as a cross-linking agent, and thiol groups are grafted onto the ends of the copolymer molecular chains, the thiol grafting density is 0.1-0.5 mmol / g, and the swelling rate of the copolymer transition layer is ≤5%.

[0013] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, the polysiloxane is an amino-modified polysiloxane with a viscosity of 500-2000 cP, the surface of the nano zinc oxide is coated with a tannic acid-silver composite layer, wherein the molar ratio of tannic acid to silver is 1:0.2-0.5, and the coating layer thickness is 2-8 nm.

[0014] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, the nano-composite protective layer is constructed by a layer-by-layer self-assembly process, each layer comprises alternately sprayed nano-zinc oxide dispersion and polysiloxane prepolymer, the spraying interval time is 10-30 seconds, the total number of layers is 5-15 layers, and the thickness of each layer is 20-50 nm.

[0015] As a further solution of the present invention: a polypropylene spunbond nonwoven fabric modified by plasma polymerization, wherein the antibacterial rate of the nonwoven fabric against Staphylococcus aureus is ≥99.5%, the antibacterial rate is maintained at ≥95% after 50 washings, and the surface hydrostatic pressure is ≥20kPa, and the air permeability is 200-500L / (m 2 ·s).

[0016] As a further solution of the present invention: a polypropylene spunbond non-woven fabric modified by plasma polymerization, the polypropylene fiber of the substrate layer is pre-irradiated with an irradiation dose of 5-20 kGy, hydroxyethyl acrylate monomer is grafted on the fiber surface with a grafting rate of 3-8%, the fiber diameter is 10-30 μm, and the porosity is 60-80%.

[0017] As a further solution of the present invention: the solid content of the nano zinc oxide dispersion in step S3 is 2-5%, the spraying rate of the polysiloxane prepolymer is 0.1-0.5 mL / min, and ultraviolet assisted crosslinking is used during curing, the ultraviolet wavelength is 365 nm, and the irradiation intensity is 50-100 mW / cm 2 .

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. This application achieves a good effect of an antibacterial rate of ≥99.5% against Staphylococcus aureus by synergizing nano zinc oxide with a tannic acid-silver composite coating layer, and the antibacterial rate of the non-woven fabric remains ≥95% after 50 washes. Tannic acid acts as a natural reducing agent and stabilizer to enhance the dispersibility and antibacterial durability of silver nanoparticles.

[0020] 2. This application imparts super-hydrophobicity with a contact angle of ≥150° to the non-woven fabric by subjecting the nano-composite protective layer to a gradient structure with a high concentration of zinc oxide and polysiloxane on the surface. At the same time, the hydrostatic pressure of the non-woven fabric is greater than or equal to 20 kPa, making the non-woven fabric both waterproof and breathable.

[0021] 3. In this application, the copolymer transition layer is cross-linked by thiol and polymerized by azobisisobutyronitrile, so that the swelling rate of the non-woven fabric is ≤5%, thereby ensuring the dimensional stability of the non-woven fabric material in a humid environment and preventing serious deformation.

[0022] 4. This application realizes plasma treatment and layer-by-layer self-assembly process, so that the entire process does not require solvents, thereby effectively reducing pollution and being environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a schematic diagram of the process of producing a polypropylene spunbond nonwoven fabric based on plasma polymerization modification. DETAILED DESCRIPTION

[0024] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0025] In the description of the present invention, it should be noted that, for those skilled in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances.

[0026] Referring to the accompanying drawings, in an embodiment of the present invention, a polypropylene spunbond nonwoven fabric modified by plasma polymerization includes a gradient functional layer, a base material layer of the gradient functional layer and a surface functional layer. The base material layer is a polypropylene nonwoven fabric, and the surface functional layer includes an inner layer, an interlayer and an outer layer.

[0027] Other embodiments of the present invention: the inner layer includes an ion activation layer, the ion activation layer has a thickness of 50-200nm, the ion activation layer is formed by argon-oxygen mixed plasma etching, the surface roughness of the ion activation layer Ra ≥ 0.5μm, wherein the surface concentration is 5-8wt% and the bottom concentration is 1-3wt%, the polypropylene fiber of the substrate layer is pre-irradiated, the irradiation dose is 5-20kGy, the fiber surface is grafted with hydroxyethyl acrylate monomer, the grafting rate is 3-8%, the fiber diameter is 10-30μm, and the porosity is 60-80%. From "Step S1: placing a polypropylene spunbond non-woven fabric substrate in a vacuum plasma reaction chamber, introducing an argon-oxygen mixed plasma mixed gas, and treating it for 5-8 minutes under conditions of power 80-120W and pressure 20-50Pa to form an ion activation layer", it can be seen that its specific production process is:

[0028] Since the inner layer is an ion activation layer formed by argon-oxygen plasma etching, the volume ratio of argon to oxygen is 4:1-8:1, the plasma treatment power is 50-150W, the treatment time is 3-10 minutes, and the surface oxygen content after etching is ≥15at%, forming a nanoscale pit array (depth 50-200nm), this embodiment specifically discloses the activation process, including the following steps:

[0029] 1.1 Substrate pretreatment

[0030] The base material is made of polypropylene spunbond non-woven fabric (weight 30g / m 2 ), after pre-irradiation treatment (conditions are cobalt-60 source, dosage is 5-20kGy), hydroxyethyl acrylate monomer is grafted on the fiber surface after irradiation, and the grafting rate is 3-8%.

[0031] 1.2 Plasma Etching

[0032] The substrate was placed in a vacuum plasma chamber and introduced into a 6:1 volume ratio Ar / O₂ mixture. The chamber pressure was 30 Pa, the power was 100 W, and the treatment time was 6 minutes. After etching, the surface roughness Ra reached 0.8 μm (measured by white light interferometry), the oxygen content increased to 18 at%, and the pit depth was approximately 150 nm.

[0033] Other embodiments of the present invention: the interlayer includes a copolymer transition layer, the copolymer transition layer has a thickness of 300-800nm, the copolymer transition layer is copolymerized by acrylic acid and vinyl pyrrolidone in a molar ratio of 1:0.3-0.8, the grafting rate of the copolymer transition layer is 25%-45% acrylic acid / vinyl pyrrolidone copolymer transition layer, 0.5-2% by mass of azobisisobutyronitrile is introduced into the copolymer transition layer as a cross-linking agent, and the ends of the copolymer molecular chains are grafted with thiol groups, the thiol grafting density is 0.1-0.5mmol / g, the swelling rate of the copolymer transition layer is ≤5%, and the specific production process is known from "step S2: mixing acrylic acid and vinyl pyrrolidone monomers in proportion, adding a cross-linking agent and an initiator, spraying them on the surface of the activation layer by atomization, and reacting at 60-80°C under a nitrogen atmosphere for 1-3 hours to form a copolymer transition layer".

[0034] Since the interlayer is an acrylic acid-vinyl pyrrolidone copolymer transition layer, and 0.5-2% azobisisobutyronitrile is introduced as a cross-linking agent, and the thiol graft density is 0.1-0.5 mmol / g, this embodiment specifically discloses the preparation process of the copolymer transition layer:

[0035] 2.1 Monomer mixing and spraying

[0036] Acrylic acid (AA) and vinyl pyrrolidone (VP) were mixed in a molar ratio of 1:0.5, and 1.5 wt% azobisisobutyronitrile (AIBN) was added as an initiator and dissolved in deionized water (solid content 10%). An ultrasonic atomization spray system was used at a spray rate of 0.3 mL / min to cover the surface of the activation layer.

[0037] 2.2 In situ polymerization and cross-linking

[0038] Under a nitrogen atmosphere, the reaction was carried out at 75°C for 2 hours to initiate free radical polymerization and form a copolymer network. Thiol groups were introduced via a thiol-ene click reaction (with the addition of 3-mercaptopropionic acid), achieving a graft density of 0.3 mmol / g (determined by the Ellman reagent method). The final transition layer thickness was 500 nm, with a swelling ratio of ≤3% (tested according to GB / T 1034).

[0039] Other embodiments of the present invention: the outer layer includes a nano-composite protective layer, the thickness of the nano-composite protective layer is 100-500nm, the nano-composite protective layer includes a complex of nano-zinc oxide with a particle size of 10-30nm and polysiloxane, the polysiloxane is an amino-modified polysiloxane, and its viscosity is 500-2000cP, the surface of the nano-zinc oxide is coated with a tannic acid-silver composite layer, wherein the molar ratio of tannic acid to silver is 1:0.2-0.5, the coating thickness is 2-8nm, wherein the mass proportion of nano-zinc oxide is 3-8%, the zinc oxide nanoparticles in the nano-composite protective layer are gradient distributed, and the surface concentration of the gradient distributed nano-zinc oxide is higher than the bottom concentration, the volume ratio of argon to oxygen in the argon-oxygen mixed plasma is 4:1-8:1, the plasma treatment power is 50-150W, the treatment time is 3-10 minutes, and the ion activation layer is 0.5-1.0. The surface oxygen content is ≥15at%, and a nanoscale pit array is formed on the surface after etching, with a pit depth of 50-200nm. The nanocomposite protective layer is constructed by a layer-by-layer self-assembly process, each layer comprising a nano-zinc oxide dispersion and a polysiloxane prepolymer sprayed alternately, the spraying interval is 10-30 seconds, the total number of layers is 5-15 layers, and the thickness of each layer is 20-50nm. The method comprises the following steps: "Step S3: alternately spraying the nano-zinc oxide dispersion and the polysiloxane prepolymer on the surface of the transition layer, curing each layer at 120-150°C for 10-30 seconds after spraying, and repeating 5-15 times to form a gradient nanocomposite protective layer, and the solid content of the nano-zinc oxide dispersion in step S3 is 2-5%, the spraying rate of the polysiloxane prepolymer is 0.1-0.5mL / min, and ultraviolet-assisted crosslinking is adopted during curing, the ultraviolet wavelength is 365nm, and the irradiation intensity is 50-100mW / cm 2 "It can be seen that its specific production process is

[0040] Since the outer layer is a nano zinc oxide / polysiloxane composite protective layer, and a layer-by-layer self-assembly process is used to construct a gradient distribution (surface concentration 5-8wt%, bottom layer 1-3wt%), this embodiment specifically discloses the process:

[0041] 3.1 Preparation of nano zinc oxide dispersion

[0042] Tannic acid-coated nano-zinc oxide particles (particle size 10-30 nm) were mixed with silver nitrate solution at a tannic acid:silver molar ratio of 1:0.3. The specific steps are as follows:

[0043] Tannic acid modification: Nano-zinc oxide was dispersed in deionized water (solid content 5%), 0.1 mol / L tannic acid solution (pH = 6) was added, and stirred at 60°C for 2 hours to form a tannic acid coating layer (thickness about 5 nm, TEM observation) by electrostatic adsorption.

[0044] Silver ion reduction: add 0.05 mol / L silver nitrate solution to the dispersion, add ascorbic acid (under the condition of molar ratio of Ag / L) under light-proof conditions. + : ascorbic acid = 1:1), reacted at 40°C for 1 hour, and silver nanoparticles (particle size 2-5 nm) were deposited on the surface of zinc oxide to form a tannic acid-silver composite coating layer (total thickness 6-8 nm, verified by EDS element mapping).

[0045] Dispersion preparation: The composite nanoparticles were washed by centrifugation and then redispersed in ethanol (solid content 3%). The mixture was ultrasonically treated (power 300 W, frequency 40 kHz) for 30 minutes to obtain a stable dispersion.

[0046] 3.2 Preparation of polysiloxane prepolymer

[0047] Use amino-modified polysiloxane and process according to the following steps:

[0048] Pre-hydrolysis: Mix polysiloxane with deionized water in a mass ratio of 10:1, add 0.5wt% acetic acid catalyst, and stir at room temperature for 2 hours to partially hydrolyze the siloxane to silanols.

[0049] Dilution adjustment: Dilute with ethanol to a viscosity of 500 cP and adjust the solid content to 8% for later use.

[0050] 3.3 Layer-by-layer self-assembly process

[0051] Use automatic spraying system for alternate spraying, the specific parameters are as follows:

[0052] First spray coating (bottom layer): Spray a nano zinc oxide dispersion at a flow rate of 0.2 mL / min, a nozzle diameter of 0.3 mm, and a spray distance of 10 cm to form a 20 nm thick bottom layer (at a nano zinc oxide concentration of 1-3 wt%). Immediately after spraying, hot air cure at 120°C for 10 seconds to initially solidify the particles.

[0053] The second layer spraying (transition layer) - spraying polysiloxane prepolymer, flow rate 0.3mL / min, after covering the zinc oxide layer, open the UV assisted crosslinking (conditions: wavelength 365nm, intensity 80mW / cm 2, 15-second exposure time) to promote siloxane condensation. Repeated spraying and gradient construction: Alternately spray zinc oxide dispersion and polysiloxane prepolymer for a total of 10 layers. Starting from the fourth layer, gradually increase the zinc oxide dispersion concentration (by 0.5wt% per layer), reaching a final surface layer concentration of 7wt%. Each layer is separated by 20 seconds, with a total thickness of approximately 400nm.

[0054] As a further solution of the present invention: a polypropylene spunbond nonwoven fabric modified by plasma polymerization, wherein the antibacterial rate of the nonwoven fabric against Staphylococcus aureus is ≥99.5%, the antibacterial rate is maintained at ≥95% after 50 washings, and the surface hydrostatic pressure is ≥20kPa, and the air permeability is 200-500L / (m 2 s), and the antibacterial performance was tested according to GB / T 20944.3, with an antibacterial rate of ≥99.8% against Staphylococcus aureus, and the antibacterial rate remained at 96.2% after 50 washes. The hydrophobicity and hydrostatic pressure resistance had a contact angle of 152° (tested according to ASTM D5946), and the hydrostatic pressure test (tested according to ISO 811) reached 22kPa. Air permeability: tested according to GB / T 5453 standard, with an air permeability of 480L / (m 2 Structural stability: After 100 bending tests (according to ASTM D2176), there is no surface cracking, and the swelling rate is ≤3.5% (according to GB / T 1034).

[0055] The working principle of the present invention is as follows: By synergizing nano-zinc oxide with a tannic acid-silver composite coating, the present invention achieves an excellent antibacterial rate of ≥99.5% against Staphylococcus aureus, and the antibacterial rate of the non-woven fabric remains ≥95% after 50 washes. Tannic acid acts as a natural reducing agent and stabilizer, enhancing the dispersibility and antibacterial durability of the silver nanoparticles. The present invention also imparts superhydrophobicity with a contact angle ≥150° and a hydrostatic pressure of ≥20 kPa by treating the nano-composite protective layer with a gradient structure. The non-woven fabric is also waterproof and breathable by maintaining a hydrostatic pressure of ≥20 kPa. The present invention also achieves a swelling rate of ≤5% by crosslinking the copolymer transition layer with thiol groups and initiating polymerization with azobisisobutyronitrile, ensuring dimensional stability in humid environments and preventing severe deformation. The present invention utilizes plasma treatment and layer-by-layer self-assembly to eliminate the need for solvents, effectively reducing pollution and improving environmental friendliness.

[0056] The above is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with this technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A polypropylene spunbond nonwoven fabric modified by plasma polymerization, comprising a gradient functional layer, a base material layer of the gradient functional layer and a surface functional layer, wherein the surface functional layer comprises an inner layer, an interlayer and an outer layer, characterized in that: The inner layer includes an ion activation layer, the ion activation layer has a thickness of 50-200 nm, the ion activation layer is formed by argon-oxygen mixed plasma etching, and the surface roughness of the ion activation layer Ra is greater than or equal to 0.5 μm; The interlayer includes a copolymer transition layer, the copolymer transition layer has a thickness of 300-800 nm, the copolymer transition layer is copolymerized by acrylic acid and vinyl pyrrolidone in a molar ratio of 1:0.3-0.8, and the grafting rate of the copolymer transition layer is 25%-45% acrylic acid / vinyl pyrrolidone copolymer transition layer; The outer layer comprises a nano-composite protective layer, the thickness of the nano-composite protective layer is 100-500nm, and the nano-composite protective layer comprises a compound of nano-zinc oxide with a particle size of 10-30nm and polysiloxane, wherein the mass proportion of the nano-zinc oxide is 3-8%.

2. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 1, characterized in that: The zinc oxide nanoparticles in the nanocomposite protective layer are distributed in a gradient manner, and the surface concentration of the gradient distributed nano zinc oxide is higher than the bottom concentration, wherein the surface concentration is 5-8wt% and the bottom concentration is 1-3wt%.

3. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 2, characterized in that: The volume ratio of argon to oxygen in the argon-oxygen mixed plasma is 4:1-8:1, the plasma treatment power is 50-150W, the treatment time is 3-10 minutes, the surface oxygen content of the ion activation layer is ≥15at%, and a nanoscale pit array is formed on the surface after etching, with a pit depth of 50-200nm.

4. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 3, characterized in that: Azobisisobutyronitrile accounting for 0.5-2% by weight is introduced into the copolymer transition layer as a crosslinking agent, and the copolymer molecular chain end is grafted with a thiol group with a thiol grafting density of 0.1-0.5 mmol / g. The swelling rate of the copolymer transition layer is ≤5%.

5. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 4, characterized in that: The polysiloxane is amino-modified polysiloxane with a viscosity of 500-2000 cP. The surface of the nano zinc oxide is coated with a tannic acid-silver composite layer, wherein the molar ratio of tannic acid to silver is 1:0.2-0.5, and the coating layer thickness is 2-8 nm.

6. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 5, characterized in that: The nanocomposite protective layer is constructed by a layer-by-layer self-assembly process. Each layer comprises alternately sprayed nano zinc oxide dispersion and polysiloxane prepolymer. The spraying interval is 10-30 seconds. The total number of layers is 5-15, and the thickness of each layer is 20-50 nm.

7. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 6, characterized in that: The antibacterial rate of the non-woven fabric against Staphylococcus aureus is ≥99.5%, and the antibacterial rate remains ≥95% after 50 washes. The surface hydrostatic pressure is ≥20kPa, and the air permeability is 200-500L / (m 2 ·s).

8. The polypropylene spunbond nonwoven fabric modified by plasma polymerization according to claim 7, characterized in that: The polypropylene fiber of the substrate layer is pre-irradiated with an irradiation dose of 5-20 kGy. Hydroxyethyl acrylate monomer is grafted on the fiber surface with a grafting rate of 3-8%. The fiber diameter is 10-30 μm and the porosity is 60-80%.

9. The polypropylene spunbond nonwoven fabric modified by plasma polymerization and the production method thereof according to claim 8, characterized in that: include Step S1: placing a polypropylene spunbond nonwoven fabric substrate in a vacuum plasma reaction chamber, introducing an argon-oxygen mixed plasma gas, and treating for 5-8 minutes at a power of 80-120 W and a pressure of 20-50 Pa to form an ion activation layer; Step S2: acrylic acid and vinyl pyrrolidone monomers are mixed in proportion, a crosslinking agent and an initiator are added, and the mixture is sprayed on the surface of the activation layer by atomization. The mixture is reacted at 60-80° C. for 1-3 hours under a nitrogen atmosphere to form a copolymer transition layer; Step S3: spraying the nano zinc oxide dispersion and the polysiloxane prepolymer alternately on the surface of the transition layer, curing each layer at 120-150° C. for 10-30 seconds after spraying, and repeating 5-15 times to form a gradient nano composite protective layer.

10. The polypropylene spunbond nonwoven fabric modified by plasma polymerization and the production method thereof according to claim 9, characterized in that: The solid content of the nano zinc oxide dispersion in step S3 is 2-5%, the spraying rate of the polysiloxane prepolymer is 0.1-0.5 mL / min, and UV-assisted cross-linking is used during curing, with an UV wavelength of 365 nm and an irradiation intensity of 50-100 mW / cm 2 .